APPROXIMATION OF THE INTEGRAL ENERGY SPECTRUM OF PROTONS OF SCR IN THE RANGE OF > 1-850 MEV - Isaeva, E. A. (Одеські астрономічні публікації, 2019)
This work is a continuation of the work (Isaeva E., 2018) in which a new approximation of the in- tegral energy spectrum of solar cosmic ray (SCR) protons was presented in the range > 1-100 MeV. In this work, the comments and wishes of colleagues working in this field were taken into account. First, the comments were taken into account on the form of the functional for approximat- ing the energy spectrum of protons, which must correspond in form to the functionals predicted by particle acceleration theories. Secondly, the previously obtained functional should be checked for high-energy protons with energies >1000 MeV. For the analysis, we used original records of the intensity of the flux of SCR protons according to the data from GOES. The studied sample contains 349 solar proton events (SPE) for the period from 03-02-1986 to 12-02-2018 years, accompanied by protons with energies in the range > 1-850 MeV. Of 349 SPE, 53 were accompanied by high- energy protons with energies > 850 MeV. In this paper, we present the results of approximation of the integral energy spectrum of SCR protons with energies > 1-850 MeV using a functional containing power and ex- ponential functions. A comparative analysis showed that this functional gives a very good approximation for SCR protons with energies in the range > 1-850 MeV.